Lower Mantle Electrical Conductivity Inferred from Probabilistic Tomography - Frédéric Deschamps (Terrestrial, Atmospheric and Oceanic Sciences, 2015)

(untitled)
Electrical conductivity is a potentially powerful observable that may be used in combination with seismological models to investigate the 3D thermo-chemical structure of the _ mantle because it depends upon both temperature and compositional parameters. Despite strong uncertainties in the lower mantle mineral conductive properties and ambiguities in choosing an appropriate average scheme to estimate the aggregate conductivity from the individual conductivities of each mineral, it is possible to calculate a radial reference model and 3D maps of electrical conductivity in the lower mantle from thermo-chemical reference models and 3D maps. This work presents a first attempt to build such models using probabilistic tomography as the input thermo-chemical structure. The radial model increases from about 0.6 S m-1 at the top of the lower mantle to 16 S m-1 at its bottom. The 3D structure shows strong lateral variations at both the top (670 - 1200 km) and bottom (2000 - 2891 km) of the lower mantle, with moderate variations in the 1200 - 2000 km layer. In the lowermost mantle (> 2000 km), which is not yet imaged yet by electrical conductivity tomographic models, a belt of high conductivity extends along the equator with relative anomalies up to 90% compared to the horizontal average.